Situational Leadership Strategy of The Principal in Improving Teachers' Discipline and Motivation at SMK Futuuhal Arifin Lembar, West Lombok - Pratama, Ahmad Ariyadi; Sulhan, Ahmad; Badrun, Badrun (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The aim of this study is to analyze the situational leadership strategy implemented by the principal in improving teachers' discipline and motivation at SMK Futuhul Arifin Lembar, West Lombok. Situational leadership is an approach that emphasizes adapting leadership styles to the prevailing circumstances and conditions. In the educational context, this is crucial to ensuring the achievement of optimal educational goals, particularly in enhancing teachers' work quality and motivation. The research employs a qualitative approach, utilizing data collection techniques such as interviews, observations, and documentation. The findings reveal that the principal of SMK Futuhul Arifin implements various strategies, including open communication, rewards, and regular coaching for teachers, which have proven effective in improving discipline and motivation. Thus, an appropriate situational leadership strategy can foster a productive work environment and enhance the quality of education in the school. This study recommends that the principal continue to develop situational leadership skills in accordance with the needs and challenges in the field.